Teaching the Basics Brilliantly or Reinforcing Yet Another Subject Hierarchy? - Wrathall, Jade (New Zealand journal of educational studies, 2024)
The New Zealand Curriculum is comprised of eight compulsory learning areas: English, the arts, health and physical education, learning languages, mathematics and statistics, science, social sciences, and technology. Collectively, these learning areas are intended to provide children with a broad and balanced education. Despite this, the National-led government have introduced a new education policy titled Teaching the Basics Brilliantly. As this policy is focused exclusively on reading, writing, mathematics, and science, a hierarchy of subjects will likely be reinforced. This article examines the different aspects of the Teaching the Basics Brilliantly policy and discusses the implications of privileging three of the eight learning areas.